The Impacts of FDI, ODA, and LS on Gross Domestic Product in Cambodia: A Comparative Analysis - Chet, Vathanak (Technium Social Sciences Journal, 2022)
The study focus mainly on the impact of ODA, FDI, and LS on the GDP growth of Cambodia from 1995 to 2020 using the combined data generated from Macrotrends LLC (2021); Trading Economics (2021); World Bank Group (2021a; 2021b; 2021c & Cambodia Public Debt Statistical Bulletin (2015; 2016; 2017; 2018; 2019; 2020; 2021) and the Eviews 10 was used as a tool to analyze the data by applying the multivariate regression with ordinary least squares method. The result confirmed that FDI and LS are significant and positively contributed to the GDP growth of Cambodia with almost 100% confident interval or probability of 0.02%, and the ODA was evidently insignificant and also negatively impacted on the economic growth of Cambodia. The researcher also suggested for further researches in order to clarify the lapses of this study.